Rekonstruktion der Oberflächenwassermassen der östlichen Laptevsee im Holozän anhand von aquatischen Palynomorphen - Kunz-Pirrung, Martina (1997)
Aquatic palynomorphs (dinoflagellate cysts, chlorococcaJ algae, acritarchs, several groups of zoomorphs) in recent and Holocene sediments of the Laptev Sea sheJf and the adjacent continental slope were studied microscopically. The data were processed by means of multivariate statistical analysis in order to define ecological preferences and to reconstruct the history of surface water masses in the eastem Laptev Sea during the Holocene. The occurrence and distribution pattern of some palynomorphs in recent sediments are clearly related to the hydrographic conditions of surface water masses. The polar surface water masses of the Laptev Sea shelf are documented in the sediments by dinoflagellate cyst assembJages with Brigantedinium spp., Algidasphaeridium? minutum and related morphotypes. lmpagidinium? pallidum, Nematosphaeropsis labyrinthus and Operculodinium centrocarpum characterize the assemblage on the continental slope. Nematosphaeropsis labyrinthus and Operculodinium centrocarpum indicate the influence of warmer Atlantic water masses. The chlorococcal algae assemblages are composed of Pediastrum spp. and Botryococcus cf. braunii which usually live in freshwater. Their occurrence in the marine environment indicates that the Laptev Sea shelf is strongly influenced by the freshwater input of the rivers OJenek, Lena and J ana. The development of the surface water masses during the last 7400 years was reconstructed in two sediment cores from the eastern Laptev Sea by qualitative and quantitative analyses of dinoflagellate cysts, chlorococcal algae and other groups of aquatic palynomorphs. Between 7400 and 7000 B.P. the sea level was 20 m beJow present level and the Lena and Yana drained through an estuary. Therefore, the influence of higher saline water masses was very low due to the freshwater inpul. Around 6400 B.P. the freshwater input into the Laptev Sea was probabely twice as high as today, indicated by the high concentrations of chlorococcal algae. At approximately the same time influence of marine water ...